2011
DOI: 10.1002/cbf.1798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on the activities of the enzymes that hydrolyse adenine nucleotides in platelets from cigarette smoke-exposed rats

Abstract: The aim of the present study was to investigate the effect of curcumin (Cur) on the activity of ectonucleoside triphosphate diphosphohydrolase (CD39), 5'-nucleotidase (CD73) and adenosine deaminase in platelets of cigarette smoke-exposed rats. For that purpose, we subjected male Wistar rats to a treatment with Cur and cigarette smoke, once a day, 5 days each week, for 30 days. The rats were treated by gavage with Cur or corn oil and then exposed to cigarette smoke. The experimental procedures were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
8
0
7
Order By: Relevance
“…However, as shown in Figure 2C , although the OB-MS group and the RW-MS can be well separated in the OPLS scores plot, CV-ANOVA test of model C in Figure 2 gives poor validity of the model suggesting that larger sample size is required to make the model performance reliable. Like adenosine derivatives, uridine has shown anti-inflammatory effects and appears to affect the tumour necrosis factor (TNF, also known as TNF-alpha) levels in lungs [ 51 ]. Elevated level of uridine and decreased level of unassigned peaks of some pyrimidine metabolites observed in this study suggested that cigarette smoke exposure can cause perturbation of pyrimidine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown in Figure 2C , although the OB-MS group and the RW-MS can be well separated in the OPLS scores plot, CV-ANOVA test of model C in Figure 2 gives poor validity of the model suggesting that larger sample size is required to make the model performance reliable. Like adenosine derivatives, uridine has shown anti-inflammatory effects and appears to affect the tumour necrosis factor (TNF, also known as TNF-alpha) levels in lungs [ 51 ]. Elevated level of uridine and decreased level of unassigned peaks of some pyrimidine metabolites observed in this study suggested that cigarette smoke exposure can cause perturbation of pyrimidine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pro‐inflammatory cytokines such as tumour necrosis factor (TNF)–alpha, the interleukin‐1 (IL‐1) family, interleukin‐6 (IL‐6) and auto‐reactive T cells have various important activities in the RA pathogenesis. In this context, the purpose of this study was to investigate the activity of purinergic system ecto‐enzymes, which are important in the regulation of immune and inflammatory responses such as E‐NTPDase and E‐ADA, in lymphocytes isolated from peripheral blood of patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…We prepared the plasma rich in platelets (PRP) as previously described [34] with modifications [35]. ATP (A6419), ADP (A2754), AMP (A1752), bovine serum albumin (BSA, A2153), trichloroacetic acid (TCA, T4885), 4-(2-hydroxyethyl)piperazine-1-ethanesulfonic acid sodium salt (HEPES-H7006) were acquired from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Assays Of Ectonucleotidase Triphosphate Diphosphohydrolase (mentioning
confidence: 99%